Hadhanah under the Islamic Law and its application in Malaysia / Zaleha Abd. Aziz - Abd. Aziz, Zaleha (Faculty of Law, 1987)
One of the important branch in the Islamic law is the Hadhanah or custody of a child and the libilities of the parents. Furthermore this is more or less the libilities of the parents that must be given to the child under their custody. The custody of a child is not only a moral obligation but also the obligation that is imposed by the Islamic Law and also the Civil so that the parents will not neglect their parental duties. Hadhanah or custody in the wider sense of the word not only entitles the parents or any others given the custody the right to legal possession and safekeeping of the child but together with it the duties and habilities to ensure the rights and wants of them. What is or is not fair to the parent in charge of t children is irrelevant because what is more important is what is best for them.